Engineering of Humanized Antibodies Against Human Interleukin 5 Receptor Alpha Subunit That Cause Potent Antibody-Dependent Cell-Mediated Cytotoxicity - Kim, Jung-Eun; Lee, Dong-Hyun; Jung, Keunok; Kim, Eun-Ji; Choi, Youngwoo; Park, Hae-Sim; Kim, Yong-Sung (Frontiers in Immunology, 2021)
Patients with severe eosinophilic asthma (SEA; characterized by persistent eosinophilia in blood and airway tissues) experience frequent asthma exacerbations with poor clinical outcomes. Interleukin 5 (IL-5) and IL-5 receptor alpha subunit (IL-5α) play key roles in eosinophilia maintenance, and relevant therapeutic strategies include the development of antibodies (Abs) against IL-5 or IL-5α to control eosinophilia. Benralizumab, an anti–IL-5α Ab that depletes eosinophils mainly via Ab-dependent cell-mediated cytotoxicity and through blockage of IL-5 function on eosinophils, has been clinically approved for patients with SEA. Here, we report engineering of a new humanized anti–IL-5Rα Ab with potent biological activity. We first raised murine Abs against human IL-5Rα, humanized a leading murine Ab, and then further engineered the humanized Abs to enhance their affinity for IL-5Rα using the yeast surface display technology. The finally engineered version of the Ab, 5R65.7, with affinity (KD ≈ 4.64 nM) stronger than that of a clinically relevant benralizumab analogue (KD ≈ 26.8 nM) showed improved neutralizing activity toward IL-5–dependent cell proliferation in a reporter cell system. Domain level Ab epitope mapping revealed that 5R65.7 recognizes membrane-proximal domain 3 of IL-5Rα, distinct from domain I epitope of the benralizumab analogue. In ex vivo assays with peripheral eosinophils from patients with SEA and healthy donors, 5R65.7 manifested more potent biological activities than the benralizumab analogue did, including inhibition of IL-5–dependent proliferation of eosinophils and induction of eosinophil apoptosis through autologous natural-killer-cell–mediated Ab-dependent cell-mediated cytotoxicity. Our study provides a potent anti–IL-5Rα Ab, 5R65.7, which is worthy of further testing in preclinical and clinical trials against SEA as a potential alternative to the current therapeutic arsenal.